KINERJA DINAS PENDIDIKAN DALAM PENYELENGGARAAN ASESMEN NASIONAL BERBASIS KOMPUTER (ANBK) DI KABUPATEN GIANYAR - Mahayoni, Gusti Ayu Dwi Intan; Yudartha, I Putu Dharmanu; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER; Vol 3 No 2 (2023): Administrasi Publik 2023, 2024)
Computer-Based National Assessment (ANBK) is an assessment system used to measure the quality of education in schools. Based on the Regulation of the Ministry of Education, Culture, Research and Technology Number 17 of 2021, one of the ANBK implementers at the district level is the Gianyar Regency Education Office. This study aims to determine the performance of the Education Office in implementing ANBK in Gianyar Regency. This type of research is qualitative research with a descriptive approach that utilizes primary and secondary data sources. Informants were determined by purposive sampling technique. This research study uses performance measurement theory according to Dwiyanto. The results showed that the performance of the Education Office in implementing ANBK in Gianyar Regency was quite good on several performance indicators, namely responsiveness and accountability. However, some performance indicators still need to be optimized, namely productivity, service quality, and responsibility in order to achieve better ANBK implementation.